Correlation between Endothelin-1 and oxidative stress in apparently healthy obese men - Malla Ahmed, Nazlin Shakir; Sulaiman, Sherwan Rahman (Zanco Journal of Medical Sciences (ZJMS), 2016)
Background and objective: Obesity is the risk for many disease conditions and is becoming a global issue. Endothelial dysfunction and oxidative stress are linked to obesity. Endothelin-1 is a useful marker of endothelial dysfunction. Oxidative stress can be assessed by estimation of lipid peroxidation byproduct malondialdehyde. In this study, we tried to find out the correlation between Endothelin-1 and oxidative stress among apparently healthy obese men. Methods: Eighty apparently healthy non-smoker adult men have participated in this study. Their age ranged between 18 and 50 years. Their serum Endothelin-1 (ELISA), malondialdehyde and lipid parameters (biochemical assays) have been estimated. Results: Subjects were divided into three groups: normal weight (n = 25), overweight (n = 34) and obese (n = 26) basing on their body mass index. The study shows that Endothelin-1 is significantly correlated with each of Malondialdehyde and body mass index (r = 0.262, P = 0.019; r = 0.65, P <0.001 respectively). Malondialdehyde is also significantly positively correlated with BMI (r = 0.378, P = 0.001). Conclusion: Endothelial dysfunction and oxidative stress coexist in obesity. But which of them precedes the other? Is still a question needs to be further studied